Stress during slaughter increases lipid metabolites and decreases oxidative stability of farmed rainbow trout (Oncorhynchus mykiss) during frozen storage. (1st January 2016) - Secci, G.; Parisi, G.; Dasilva, G.; Medina, I.
Highlights: Rainbow trout slaughtered by asphyxia or percussion have been considered. 12 lipid mediators from EPA, ARA, and DHA were found. 12-HpEPE/15-HpEPE and PGE3 /PGD3, EPA-derived, could be considered stress biomarkers. DHA was found to be a fairly good substrate of LOX. Slaughtering methods can largely affect oxidative stress and oxidative stability. Abstract: The consequences of slaughter on the formation of lipid metabolites and oxidative stability of fish muscle during long term frozen storage (−10 °C) were evaluated using farmed rainbow trout killed by asphyxia in air or percussion. The level of major adenine nucleotides and their related compounds was determined in order to check the stress level during slaughter. Plasma lipid metabolites were studied through the determination of eicosanoids and docosanoids such as prostaglandins, leukotrienes, thromboxanes, isoprostanes, resolvins, hydroxides, hydroperoxides, coming from eicosapentaenoic (EPA), arachidonic (ARA), and docosahexaenoic (DHA) acids. In addition, lipid oxidative stability of fillets was monitored. Results revealed that stress during slaughter can greatly influence oxidative stress and oxidative stability of rainbow trout fillets. In fact, asphyxia, which was the most stressful, induced a higher production of some lipid mediators such as hydroperoxides and EPA-derived prostaglandins, such as 12-HpHEPE/15-HpHEPE and PGD3 /PGE3 . As a consequence, fillets derived from asphyxiated fish were less stable in terms of oxidative stability and showed lower shelf-life.